Cost-Effectiveness of Various Diagnostic Approaches for Occupational Asthma - Wendy A Kennedy; Frédéric Girard; Simone Chaboillez; André Cartier; Johanne Côté; Frederick Hargreave; Manon Labrecque; Jean-Luc Malo; Susan M Tarlo; Carrie A Redlich; Catherine Lemière (Canadian Respiratory Journal)
BACKGROUND: Diagnosis of occupational asthma (OA) by specific inhalation challenge (SIC) can be costly and is not always available. The use of sputum testing to avoid this in some patients may be a more cost-effective alternative.